Kinetics of intracolloidal iodine in thyroid of iodine-deficient or equilibrated newborn rats. Direct imaging using secondary ion mass spectrometry - Elbast, M.; Wu, T.D.; Guiraud-Vitaux, F.; Guerquin-Kern, J.L.; Petiet, A.; Hindie, E.; Champion, C.; Croisy, A.; Colas-Linhart, N. (Cellular and Molecular Biology, 2007)
The most significant impact of the Chernobyl accident is the increased incidence of thyroid cancers among children. In order to accurately estimate the radiation dose provided by radioiodines, it is important to examine how the distribution of newly incorporated iodine varies with time and if this distribution varies according to the iodine status. The kinetic distribution of intra colloidal newly organified iodine in the rat immature thyroid was recorded and analysed using the ionic nanoprobe NanoSims50. Our observations imply that in case of radioiodine contamination, the energy deposits vary (i) with time, (ii) from one follicle to another, and (iii) from one cell to another inside the same follicle regardless the iodine status. The kinetic heterogeneity of iodine distribution must be take in account in thyroid dose evaluation.